Early Childhood Field-based Initial Teacher Education in New Zealand. A Valid Choice? - Christine Coombes; Nicole Downie (New Zealand Journal of Teachers' Work)
This article provides an insight into the background and philosophy of field-based teacher education in the early childhood sector. Throughout, we discuss why such programmes should be considered as a valid choice for both students and ITE providers.